Vaccine therapies for glioma: clinical frontiers and potential breakthrough - Xing, Ying; Liu, Caixia; Feng, Yunfeng; Li, Shangyu; Chen, Yuping (Frontiers in Oncology, 2025)
Glioma, the most common primary malignant brain tumor, is characterized by high recurrence and mortality rates. Its effective treatment remains a therapeutic challenge in clinical neuro-oncology. Despite over twenty years of exploring new therapies for glioma, progress in improving patient survival outcomes has been limited. Tumor vaccines, as a promising therapeutic approach, may offer hope for glioma treatment. Currently, tumor vaccines targeting glioma include peptide vaccines, dendritic cell vaccines, and nucleic acid vaccines. Neoantigens, due to their high specificity and resistance to central immune tolerance, are ideal targets for tumor vaccines. Although promising results have been resulted in preclinical and clinical for glioma vaccines, there are still challenges impeding vaccine therapy for glioma. Therefore, future glioma vaccine applications must focus on the important roles of epitope spreading and antigen quality in enhancing immune response and therapeutic effectiveness. In this review, we discuss the current glioma vaccine antigen targets and types, introduce recent important clinical studies on glioma vaccines, and propose strategies to address potential barriers to vaccine application.